Evaluation of the outcome of pyeloplasty in children with poorly functioning kidneys due to unilateral ureteropelvic junction obstruction - Rohit Kapoor; Amit Gupta; Pooja Abbey; Ravinder Singh Sethi; Partap Singh Yadav; Subhasis Roy Choudhury; Rajiv Chadha (Wolters Kluwer Medknow Publications, 2022)
Aim: To analyze the outcome of upfront pyeloplasty in kidneys of children with unilateral ureteropelvic junction obstruction (UPJO). Materials and Methods: Thirty-three consecutive cases with split renal function (SRF) of ≤20% on dynamic renal scintigraphy (DRS) underwent upfront pyeloplasty with a nephrostomy tube and trans-anastomotic stent. Outcome was analyzed based on symptomatic relief, nephrostomy output, surgical complications and changes noted in pre-and post-operative findings on renal ultrasound (US), and DRS. Results: The most common symptom was abdominal lump in <5-year age group (79%) and abdominal pain in >5-year age group (93%). Postoperatively, symptoms were relieved in all (100%), parenchymal thickness (PT) on US improved in 82% and SRF improved significantly (>5%) in 75.8% of patients. The improvement was more significant in patients with abdominal lump and large kidneys. The mean nephrostomy output showed an inverse relationship with age at pyeloplasty and a direct correlation with the change in PT and SRF. The degree of improvement in SRF also was inversely related to the age at pyeloplasty with a significantly better outcome in <2-year-age. Although age at pyeloplasty, nephrostomy output and change in PT individually showed significant correlation with change in SRF, multiple regression analysis showed PT as the only significant factor. Conclusion: Upfront pyeloplasty should be the first option in children with poorly functioning kidneys as it has a favorable outcome in almost all the cases with a very low incidence of complications. The degree of improvement in SRF can be predicted by the nephrostomy output and improvement in PT on US.